2006
DOI: 10.1097/01.wnn.0000209875.56060.06
|View full text |Cite
|
Sign up to set email alerts
|

Volition and Imagery in Neurorehabilitation

Abstract: New interventional approaches have been proposed in the last few years to treat the motor deficits resulting from brain lesions. Training protocols represent the gold-standard of these approaches. However, the degree of motor recovery experienced by most patients remains incomplete. It would be important to improve our understanding of the mechanisms underlying functional recovery. This chapter examines the role of two possible mechanisms that could operate to improve motor function in this setting: volition a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
69
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(75 citation statements)
references
References 66 publications
4
69
0
2
Order By: Relevance
“…More specifically, difficulties imagining future pleasant events, and particularly poor selfreferential information for future pleasant events (i.e., the feelings of pre-experiencing positive events, the feeling of an emotion when imagining a pleasant event and the representation of one's own behavior), were associated with motivation deficits in pursuing personal goals in schizophrenia patients. The relationships between poor representation of one's own behavior in the future and apathy can be interpreted according to a well-known cognitive theory of motor cognition that suggests that cognition is embodied in action and that the ability to vividly simulate acting in the future could actually lead to increased action (Lotze and Cohen, 2006). In other words, the ability to imagine oneself performing (i.e., pre-experiencing) a possible future action could facilitate the later reproduction of this action, by increasing one's motivation and effort to attain imagined future goals and by prompting the effective motor sequences/behaviors needed to achieve these goals (D'Argembeau and Van der Linden, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, difficulties imagining future pleasant events, and particularly poor selfreferential information for future pleasant events (i.e., the feelings of pre-experiencing positive events, the feeling of an emotion when imagining a pleasant event and the representation of one's own behavior), were associated with motivation deficits in pursuing personal goals in schizophrenia patients. The relationships between poor representation of one's own behavior in the future and apathy can be interpreted according to a well-known cognitive theory of motor cognition that suggests that cognition is embodied in action and that the ability to vividly simulate acting in the future could actually lead to increased action (Lotze and Cohen, 2006). In other words, the ability to imagine oneself performing (i.e., pre-experiencing) a possible future action could facilitate the later reproduction of this action, by increasing one's motivation and effort to attain imagined future goals and by prompting the effective motor sequences/behaviors needed to achieve these goals (D'Argembeau and Van der Linden, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The motor images require conscious activation of brain regions that are also involved in the preparation and performance of the movement, accompanied by a voluntary inhibition of the real movement (Lotze and Cohen 2006). Studies have shown that there is similarity in the physiological and psychophysical functions between executed and imagined movements, suggesting that they are based on the same process.…”
Section: Introductionmentioning
confidence: 99%
“…Motor Imagery (MI) corresponds to an active process during which the representation of a specific action is internally reproduced into working memory without any motor output (Deepa et al, 2011;Lotze and Cohen, 2006;Dietrich, 2008). It represents the result of conscious access to the content of a movement intention, which is usually performed unconsciously during movement preparation (Gentili et al, 2006;Jackson et al, 2001;Dietrich, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Predominantly left lateralised, the ventro-dorsal stream extends from occipital cortex to the left IPL, to the ventral premotor cortex and frontal eye fields (Frey 2007;Rizzolatti, Fogassi, & Luppino, 2011). The ventro-dorsal stream is purportedly critical in skilled action execution, movement perception, and mental representations of movement (or motor imagery) that may be necessary when retrieving postural requirements related to skilled object-use and object manipulation (Jeannerod, 1994;Buccino et al, 2001;Kosslyn, Ganis, & Thompson, 2001;Solodkin, Hlustik, Chen, & Small, 2004;Johnson-Frey, Newman-Norland, & Grafton, 2005;Buxbaum, Kyle, Tang, & Detre, 2006;Lotze & Cohen, 2006;Creem-Regehr, 2009;Rizzolatti & Craighero, 2004;Buxbaum & Kalénine, 2010;Gao, Duan, & Chen, 2011). It is therefore possible that skilled action execution, motor imagery and movement perception may involve a common process that critically relies on the ventrodorsal stream.…”
Section: Introductionmentioning
confidence: 99%